Nanotechnology for water treatment and purification - Apblett, Allen; Hu, Anming (Lecture Notes in Nanoscale Science and Technology, 2014)
This book describes the latest progress in the application of nanotechnology for water treatment and purification. Leaders in the field present both the fundamental science and a comprehensive overview of the diverse range of tools and technologies that have been developed in this critical area. Expert chapters present the unique physicochemical and surface properties of nanoparticles and the advantages that these provide for engineering applications that ensure a supply of safe drinking water for our growing population. Application areas include generating fresh water from seawater, preventing contamination of the environment, and creating effective and efficient methods for remediation of polluted waters. The chapter authors are leading world-wide experts in the field with either academic or industrial experience, ensuring that this comprehensive volume presents the state-of-the-art in the integration of nanotechnology with water treatment and purification. Covers both wastewater and drinking water treatment Provides concise yet thorough coverage of the fundamentals of nanomaterials and treatment processes as well as insights into future R&D trends Presents the latest progress in research and prototype testing lines Written for a broad audience of engineers, researchers, municipal water managers, and policymakers